Comparative Study of Ectopic Lymphoid Aggregates in Sheep and Murine Models of Bleomycin-Induced Pulmonary Fibrosis - Udari Eshani Perera; Louise Organ; Simon G. Royce; Chrishan S. Samuel; Habtamu B. Derseh; Sasika N. V. Dewage; Emmanuel Koumoundouros; Andrew Stent; Kenneth J. Snibson (Canadian Respiratory Journal)
Idiopathic pulmonary fibrosis (IPF) is a chronic disease characterized by excessive deposition of extracellular matrix in the interstitial lung parenchyma, often manifested by dyspnea and progressive loss of lung function. The role of inflammation in the pathogenesis of IPF is not well understood. This study evaluated the histopathological and inflammatory components of bleomycin-induced pulmonary fibrosis in mouse and sheep models, in terms of their ability to translate to the human IPF. Merino sheep (n = 8) were bronchoscopically administered with two bleomycin infusions, two weeks apart, into a caudal lung segment, with a saline (control) administered into a caudal segment in the opposite lung. Balb/c mice were twice intranasally instilled, one week apart, with either bleomycin (n = 7); or saline (control, n = 7). Lung samples were taken for the histopathological assessment 28 days in sheep and 21 days in mice after the first bleomycin administration. We observed tertiary lymphoid aggregates, in the fibrotic lung parenchyma of sheep, but not in mouse lung tissues exposed to bleomycin. B-cell and T-cell infiltration significantly increased in sheep lung tissues compared to mouse lung tissues due to bleomycin injury. Statistical analysis showed that the fibrotic score, fibrotic fraction, and tissue fraction significantly increased in sheep lung tissues compared to murine lung tissues. The presence of tertiary lymphoid aggregates in the lung parenchyma and increased infiltration of T-cells and B-cells, in the sheep model, may be useful for the future study of the underlying inflammatory disease mechanisms in the lung parenchyma of IPF patients.